The Influence of Leadership, Motivation, Work Ability and Work Environment on Employee Performance in the Office of the National Narcotics Agency of North Labuhanbatu Regency - Arsal, Surya; Nasution, Meisa Fitri; Prayoga, Yudi (Budapest International Research and Critics University, 2022)
This research was conducted with the aim of knowing the effect of leadership, motivation, work ability and work environment on employee performance at the office of the National Narcotics Agency of North Labuhanbatu Regency. The method used is a quantitative method, with the help of the IBM SPSS 25 Software analysis tool. The data in this research is analyzed using several techniques, such as classical assumption test, multiple linear regression analysis, hypothesis testing, and coefficient of determination test. The results of the study stated that all independent variables had a positive and significant effect on employee performance. This is proven byleadership variable (X1) has a value of tcount (2.48) > ttable (1.70) with a significant value less than the probability value of 0.05 or a significant value of 0.019 <0.05, it can be concluded that the leadership variable (X1) has a positive and significant effect on employee performance. Motivation (X2) has a value of tcount (2,68) > ttable (1.70)with a significantly smaller value than the probability of 0.05 or 0.012 <0.05, it can be concluded that motivation (X2) has a positive and significant effect on employee performance. Workability (X3) has a value of tcount (5,14) > ttable (1.70)which means Ha is accepted and Ho is rejected with a significantly smaller value than the probability of 0.05 or 0.000 <0.05, it can be concluded that work ability (X3) has a positive and significant effect on employee performance. The work environment (X4) has a value of tcount (8.04) > ttable (1.70) with a significantly smaller value than the probability of 0.05 or 0.000 <0.05, it can be concluded that the work environment (X4) has a positive and significant effect on employee performance. The results of the F test show an Fcount of 49.55 > Ftable 2.71 with a significance value of 0.000 <0.05. From these results, it can be concluded that leadership, motivation, work ability and work environment simultaneously have a positive and significant effect on employee performance.